Synapse biology in the 'circuit-age'—paths toward molecular connectomics. (February 2017) - Schreiner, Dietmar; Savas, Jeffrey N; Herzog, Etienne; Brose, Nils; de Wit, Joris
Highlights: The CNS represents a precisely organized synaptic network formed by diverse neurons. Neuronal adhesion proteins substantially contribute to synaptic complex organization. Molecular compositions of synaptic complexes define their functional capabilities. New techniques will help to gain insight in the molecular organization of synapses Abstract : The neural connectome is a critical determinant of brain function. Circuits of precisely wired neurons, and the features of transmission at the synapses connecting them, are thought to dictate information processing in the brain. While recent technological advances now allow to define the anatomical and functional neural connectome at unprecedented resolution, the elucidation of the molecular mechanisms that establish the precise patterns of connectivity and the functional characteristics of synapses has remained challenging. Here, we describe the power and limitations of genetic approaches in the analysis of mechanisms that control synaptic connectivity and function, and discuss how recent methodological developments in proteomics might be used to elucidate the molecular synaptic connectome that is at the basis of the neural connectome.